Osornodella gabrielae, n. gen. and n. sp., a new falklandellid (Amphipoda: Gammaridea) from freshwaters of the Chilean Coastal Range - Pérez-Schultheiss, Jorge (Zootaxa, 2013)
The first species of falklandellid amphipod outside the Falkland Islands: Osornodella gabrielae n. gen., n. sp. is described from freshwaters of subterranean origin in the Coastal Range of Osorno province, Chile. The new taxon is characterized principally by the absence of secondary sexual characters in pereopods 3–4, uropod 3 aequiramous and telson slightly cleft. The new species is described and illustrated and its morphological relationships with other known species of this group are discussed.